Pelatihan Keterampilan Berbahasa Inggris dalam Materi Perkenalan melalui Video Pembelajaran pada SMP N 1 Buay Madang - Ainur Rohmah; Muhammad Muklas; Jelita Jelita (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) STKIP Nurul Huda, 2022)
The objective of this program to increase the students skill for learning English using video, at the students of Junior high school one Buay Madang, especially seventh c. The material is Introduction for having sprits and motivations in Learning English. According to the process teaching and learning program the students having been enthusiastic for knowing the materials. The students have a big spirit to try getting the introduction after watching the videos.